"IMPROVING THE METHODOLOGY OF TEACHING THE SUBJECT" HISTORY OF UZBEKISTAN " IN THE DEVELOPMENT OF SOCIALLY ACTIVE CIVIC COMPETENCE OF STUDENTS” (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
One of the prerequisites in the world is the creation of socially active civil competence, which is important to increase human capital (Human Capital)2 in the development of the abilities of young people of the 21st century to actively participate in scientific research in the “Data science”1 Direction. Particular attention is paid to the fact that the social activism of each citizen in the requirements set out in the Copenhagen Council's document 3 on the criteria of humanity is an indicator that determines the progress of society. In this regard, the formation of leadership qualities in young people, their upbringing as a socially active person, through an excellent study of the history of the motherland, national spirituality, is gaining special relevance.